1997
DOI: 10.5737/1181912x73140143
|View full text |Cite
|
Sign up to set email alerts
|

Getting to know oncology inpatients and their families: A continuous quality improvement approach

Abstract: Given the overall magnitude of cancer, a climate of stretched health care resources, and the political activism of cancer survivors and families, it is becoming increasingly clear that local service providers need to assess and reassess the care they provide. A qualitative design was used to seek the patient and family's perspectives on whether or not their needs were being met while in hospital. Direct feedback from a convenience sample of 19 oncology patients and families was elicited through a semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The survivors of childhood brain tumors become more concerned about their physical HRQOL as they move into adolescence and young adulthood. 14, 15 Our own research identified the importance of late effects for explaining their reports of HRQOL. 5 …”
Section: Conceptual Frameworkmentioning
confidence: 91%
“…The survivors of childhood brain tumors become more concerned about their physical HRQOL as they move into adolescence and young adulthood. 14, 15 Our own research identified the importance of late effects for explaining their reports of HRQOL. 5 …”
Section: Conceptual Frameworkmentioning
confidence: 91%